2020
DOI: 10.2147/cmar.s281578
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA SNHG22 Induces Cell Migration, Invasion, and Angiogenesis of Gastric Cancer Cells via microRNA-361-3p/HMGA1/Wnt/β-Catenin Axis</p>

Abstract: Background The correlation between long non-coding RNAs (lncRNAs) and gastric cancer (GC) has been indicated. As a newly found lncRNA, small nucleolar RNA host gene 22 (SNHG22) functions as an oncogene in ovarian carcinoma and breast cancer. However, its action has not been explored in GC. Herein, the purpose of the current research was to examine the influence of SNHG22 on GC development. Methods RT-qPCR was used to identify SNHG22 and microRNA-361-3p (miR-361-3p) in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Recently, Shen et. al demonstrated that SNHG22 induces migration, invasion and angiogenesis of gastric cancer cells via miR-361-3p/HMGA1/Wnt axis [ 29 ]. However, the mechanism for high SNHG22 expression remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shen et. al demonstrated that SNHG22 induces migration, invasion and angiogenesis of gastric cancer cells via miR-361-3p/HMGA1/Wnt axis [ 29 ]. However, the mechanism for high SNHG22 expression remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNF144A-AS1 binds to miR-361-3p and reduces the expression of the latter. miR-361-2p has low expression in malignant solid tumors such as prostate cancer (51), ovarian cancer (52), GC (53), non-small cell lung cancer (54,55) and has been con rmed as a tumor suppressor. In this study, it was found that miR-361-3p was low expressed in GC tissues and negatively correlated with RNF144A-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“… 67 lncRNA SNHG22 can upregulate HMGA1 through sponge miR-361-3p to activate Wnt/β-catenin pathway, thereby promoting GC progression ( Figure 2 C). 64 1,081 lncRNAs, 127 microRNAs, and 1,983 differentially expressed mRNAs were screened from RNA-seq data of hepatocellular carcinoma (HCC) patients in the TCGA database. More importantly, lncRNA MYLK-AS1/miR-424-5p/E2F7 axis was the only ceRNA regulatory axis negatively correlated with OS.…”
Section: Correlation Between Lncrnas and Angiogenesis In Cancermentioning
confidence: 99%